2017
DOI: 10.1186/s12967-017-1170-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of atrial fibrillation susceptibility genes, atrial fibrillation phenotypes and response to catheter ablation: a gene-based analysis of GWAS data

Abstract: BackgroundPrevious studies have suggested PITX2, KCNN3 and ZFHX3 as atrial fibrillation (AF) susceptibility genes. Single common genetic polymorphisms of those genes have been linked with AF phenotypes and rhythm outcome of AF catheter ablation although their mechanisms remain elusive. New gene-based association tests may help clarifying genotype–phenotype correlations. Therefore, we hypothesized that PITX2, KCNN3 and ZFHX3 associate with left atrial enlargement and persistent AF and subsequently with ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…There are several limitations that are comparable to our previous study (Husser et al, 2017 ). This study included small sample size.…”
Section: Limitationssupporting
confidence: 81%
See 1 more Smart Citation
“…There are several limitations that are comparable to our previous study (Husser et al, 2017 ). This study included small sample size.…”
Section: Limitationssupporting
confidence: 81%
“…We have previously applied gene-based testing to analyze the association between AF susceptibility genes PITX2, KCNN3 , and ZFHX3 and left atrial diameter (LAD), AF type and AF recurrence after ablation. Among the three candidate genes, only ZFHX3 associated with LA dilatation and AF recurrence after catheter ablation (Husser et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Important candidates identified by other studies which are not part of calcium signaling and ECM–receptor interaction were beyond the focus of our study. PITX2 , ZFHX3 , and KCNN3 were analyzed in a single gene approach as recently published by our group ( Husser et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the invasive nature of RFCA, as well as the significant cost, the need for improved strategies to guide patient selection between ablative vs nonablative options is crucial . Several genome‐wide association studies regarding AF have reported that harboring common genetic variants could significantly increase AF recurrence rates . These genetic variants are mainly involved in inflammatory‐related pathways, which are related to the initiation and progression of AF by several mechanisms such as the promotion of structural remodeling of the left atrium .…”
Section: Introductionmentioning
confidence: 99%